Contributo para o estudo do Monte do Castelo de Fraião, Boivão, Valença - Martins, Carla Maria Braz (Portvgalia : Revista de Arqueologia do Departamento de Ciências e Técnicas do Património da FLUP, 2018)
The hill of the Castle of Fraião, also denominated Castle of Furna, is located in Boivão, Valença, Viana do Castelo. In this place it took place an archeological intervention in the year 2000, being exhumed abundant ceramic materials of medieval age and a beautiful belt plate in copper and gold of the same period.